2017
DOI: 10.1039/c7ra00227k
|View full text |Cite
|
Sign up to set email alerts
|

A dual-emitting core–shell carbon dot–silica–phosphor composite for LED plant grow light

Abstract: Light-emitting diodes (LEDs) are widely used for artificial lighting in plant factories and have been applied for disease prevention and for accelerating plant growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…58,59 The red-emitting CaAlSiN 3 :Eu 2+ phosphor and blue-emitting CDs were connected through a silica framework to form a CDs/ CaAlSiN 3 :Eu 2+ -silica powder. 35 The powder has red and blue dual-emission properties. The LED devices fabricated with the powder are used for lighting plant growth in plant factories.…”
Section: Light Conversion Film and Light-emitting Diodes Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…58,59 The red-emitting CaAlSiN 3 :Eu 2+ phosphor and blue-emitting CDs were connected through a silica framework to form a CDs/ CaAlSiN 3 :Eu 2+ -silica powder. 35 The powder has red and blue dual-emission properties. The LED devices fabricated with the powder are used for lighting plant growth in plant factories.…”
Section: Light Conversion Film and Light-emitting Diodes Devicesmentioning
confidence: 99%
“…In addition, the red fluorescence‐rare earth nanocomposites were prepared by connecting red‐emitting rare‐earth nanocomposites with blue fluorescence CDs through a silica connecting layer to obtain both blue‐ and red‐emitting complex film 58,59 . The red‐emitting CaAlSiN 3 :Eu 2+ phosphor and blue‐emitting CDs were connected through a silica framework to form a CDs/CaAlSiN 3 :Eu 2+ ‐silica powder 35 . The powder has red and blue dual‐emission properties.…”
Section: Effects Of Fluorescent Cds On the Preharvest Process Of Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the nanocomposite properties, such fluorescence and Cu 2+ sensing selectivity and sensibility can be regulated through the C‐dots/APTES ratio. A dual emitting core‐shell C‐dots/CaAlSiN 3 : Eu 2+ ‐silica phosphor nanocomposite has been used to produce LED light for plant grow …”
Section: Nanocompositesmentioning
confidence: 99%